Harmonic scalpel compared with conventional open (Milligan-Morgan) method in surgical management of symptomatic haemorrhoids - G. V., Ravi Kumar; S., Madhu B.; Tanga, Vishal; Reddy M., Naveen Kumar; Pawar, Praveen M. (International Surgery Journal, 2017)
Background: There have been many attempts to find less painful surgical methods for treating haemorrhoids. Harmonic scalpel is a device that simultaneously cuts and coagulates soft tissues through ultrasonic vibrations. The aim of this study was to compare the results of Harmonic scalpel hemorrhoidectomy with conventional Milligan Morgan hemorrhoidectomy for the treatment of grade III and IV hemorrhoids. Methods: Patients with grade III or IV hemorrhoids, operated between January 2016 and December 2016, using the harmonic scalpel (n=30) or the conventional open technique (n=30) were studied. Both the groups were compared with respect to Operative time, Blood loss during surgery, early postoperative complications, postoperative pain measured on a visual analog scale (VAS), hospital stay, and return to normal work. Results: Harmonic scalpel and conventional open haemorrhoidectomy patients differ significantly in terms of VAS score of postoperative pain, blood loss during surgery, early post-operative complications, return to normal work. However, there is no significant difference in terms of duration of surgery and hospital stay in both the groups. Conclusions: Harmonic scalpel haemorrhoidectomy has been found advantageous method when assessing the amount of bleeding intraoperatively, post-operative pain, early postoperative complications, and Return to normal work. Hence Harmonic scalpel haemorrhoidectomy can be adapted as a safe and effective alternate method for treating symptomatic haemorrhoids.